Epitope Mapping of a Protective Monoclonal Antibody against Pneumocystis carinii with Shared Reactivity to Streptococcus pneumoniae Surface Antigen PspA - Wells, Jesse (American Society for Microbiology, 2004)
Pneumocystis carinii is an opportunistic fungal pathogen that causes pneumonia in the immunocompromised host. A protective monoclonal antibody (MAb) termed 4F11 generated against mouse-derived P. carinii was shown by indirect immunofluorescence assay (IFA) to bind surface antigens of P. carinii derived from multiple host species, including humans. We have identified multiple epitopes recognized by MAb 4F11 in two recombinant mouse P. carinii antigens. The epitopes mapped have similar proline content and positive charge distribution. The consensus 8-mer epitope recognized by MAb 4F11 is K/RPA/RPK/QPA/TP. Immune sera raised against intact mouse P. carinii recognized native antigens affinity purified with MAb 4F11 and a recombinant antigen reactive with MAb 4F11. Database searches for short, nearly exact matches to the mapped MAb 4F11 epitopes identified a bacterial surface antigen, Streptococcus pneumoniae PspA, with a similar proline-rich region. In an IFA, MAb 4F11 detected antigens on the S. pneumoniae surface, and Western blotting identified a protein in S. pneumoniae lysates consistent with the M(r) of PspA. A fragment of the S. pneumoniae PspA gene was cloned and sequenced, and the deduced amino acid sequence contained a region with strong similarity to the MAb 4F11 epitopes identified in P. carinii. The PspA recombinant polypeptide was recognized by MAb 4F11 in a Western blot. The ability of MAb 4F11 to recognize similar proline-rich epitopes may explain its ability to recognize P. carinii derived from multiple hosts and will permit testing of the epitopes recognized by this antibody in immunization against P. carinii.